If only [videorecording (DVD)] - Junger, Gil; Junger, Gil; Hewitt, Jennifer Love, 1979-; Hewitt, Jennifer Love, 1979-; Nicholls, Paul, 1979-; Davenport, Lucy; Wilkinson, Tom, 1948- (Sony Pictures Home Entertainment, 2006)
A talented young singer/songerwriter had met the love of her life while studying classical music in London. Unfortunately, the two have a terrible argument and she becomes involved in a terrible accident. But when fate miraculously intervenes, her grief-stricken boyfriend gets a second chance to relive the tragic day - and hopefully change their destiny.